2016
DOI: 10.1111/1471-0307.12349
|View full text |Cite
|
Sign up to set email alerts
|

Milk quality characteristics of Boutsiko, Frisarta and Karagouniko sheep breeds reared in the mountainous and semimountainous areas of Western and Central Greece

Abstract: In this study, the chemical and microbiological characteristics of ovine milk from three indigenous Greek breeds was assessed. The breeds selected for this study were Boutsiko, Frisarta and Karagouniko. The milk yield of each breed was recorded at the early, mid‐ and late stages of lactation for two consecutive years. Among the three breeds, the average milk compositions obtained were similar for protein, lactose and total solids; however, fat values were significantly lower in Frisarta milk compared with Bout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(67 reference statements)
1
11
0
1
Order By: Relevance
“…Of the 15 different FAs identified in milk samples, only nine showed statistically significant differences among breeds. The percent composition of FAs in the present study is in good agreement with the results in the literature …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Of the 15 different FAs identified in milk samples, only nine showed statistically significant differences among breeds. The percent composition of FAs in the present study is in good agreement with the results in the literature …”
Section: Resultssupporting
confidence: 92%
“…Previous studies dealing with the determination of conventional quality parameters of milk samples from various Greek sheep breeds showed a significant variation in pH, lactose, proteins and total solids . Such variations in milk physicochemical parameters have been reported to depend on different factors such as sheep breed, diet, season, reproduction period, management practices, sheep health status and environmental conditions …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The supplementation of feeds with fish oil, which is rich in MUFA and PUFA, affected the lipogenic genes of mammary gland and decreased the fat content of the ovine milk (Carreño et al, 2016). Previous studies on conventional feeding (hay and concentrates) of lactating Karagouniko ewes on the milk composition revealed that the fat content of the milk was dependent on the type of concentrates (Papadopoulos et al, 2002;Sinanoglou et al, 2015 ;Skoufos et al, 2017).…”
Section: Resultsmentioning
confidence: 99%